Preparation of Anti-Zearalenone IgY and Development of an Indirect Competitive ELISA Method for the Measurement of Zearalenone in Post-Fermented Tea - Taotao Qiu; Huayi Zhang; Hongtao Lei; Lin Zhang; Yaqiong Zhang; Xing Shen; Biyun Xu; Jialin Zhu; Wentao Xiao; Jixu Zheng; Jiahong Chen (Foods, 2023)
Post-fermented tea (PFT) is one of the most commonly consumed beverages worldwide. Rapid microbial growth and significant changes in the microbial composition of PFT during processing and storage pose a potential risk of contamination with mycotoxins such as zearalenone (ZEN). Screening for ZEN contamination in a simple, rapid, and inexpensive manner is required to ensure that PFT is safe for consumption. To monitor ZEN in PFT, ZEN was conjugated with bovine serum albumin to prepare egg yolk immunoglobulins (IgY). A specific indirect competitive enzyme-linked immunosorbent assay (ic-ELISA) based on IgY was developed and validated. ZEN was extracted with acetonitrile and water (50:50, v/v) containing 5% acetic acid and purified using a mixture of primary and secondary amines and graphitized carbon black to remove matrix interference from the PFT samples. Under optimal conditions, the linear range of this assay was 13.8−508.9 ng mL−1, the limit of detection was 9.3 ng mL−1, and the half-maximal inhibitory concentration was 83.8 ng mL−1. Cross-reactivity was negligible, and the assay was specific for ZEN-related molecules. The recovery rate of ZEN in the control blanks of PFT samples spiked with a defined concentration of ZEN of 89.5% to 98.0%. The recovery and accuracy of the method were qualified for PFT matrices. No significant differences were evident between the results of the actual PFT samples analyzed by high-performance liquid chromatography and ic-ELISA. The collective data indicate that the developed ic-ELISA can be used for the rapid and simple detection of ZEN in PFT products.